Relocation of bioclimatic suitability of Portuguese grapevine varieties under climate change scenarios - Adão, Filipe; Campos, João C.; Santos, João A.; Malheiro, Aureliano C.; Fraga, Hélder (Frontiers in Plant Science, 2023)
Climate change has been driving warming trends and changes in precipitation patterns and regimes throughout Europe, which have been affecting viniculture and winemaking. Climate change projections suggest the strengthening of these trends in the future, particularly challenging the sustainability of viniculture in southern Europe. Significant efforts toward adaptation should be then carried out. To help with the decision-making process, Ecological Niche Models were conducted to model the current bioclimatic envelope of twelve Portuguese grape varieties from the main wine regions in Portugal, Spain, France, and Italy. The models were then projected to 2051–2080 to better understand the bioclimatic shifts under climate change (RCP4.5 and RCP8.5 scenarios). Four bioclimatic indices were used for this purpose, namely the Huglin Index, the Cool Night index, the Growing Season Precipitation index, and the Temperature Range during Ripening index. The models were built using BIOMOD2 and performed with high statistical accuracy. The respective projections were able to discriminate several suitable bioclimatical areas for the grape varieties, in and around where they are currently located but also remote ones. The distribution of these areas changed, however, when looking at future projections. For both climatic scenarios, projected suitabilities suffer a considerable shift to the north of Spain, while some completely shift to France. In some cases, climatic suitabilities also tend towards areas of higher elevation. Portugal and Italy barely retain any of the initially projected varietal areas. These results show the usefulness of the selected methodology and its ensemble approach to assert potential bioclimatic suitability and fluctuations crucial for the sustainability and adaptation of cultivation activities. The obtained models were highly informative and can serve the purpose of understanding the dynamics of bioclimatic suitability with changing climates of not only grape varieties, but also other agricultural varieties with relevant economic importance.